Kearifan Syariat dan Hikmah dalam Puasa - Mufaizin , Mufaizin (LPPPM STAI Darul Hikmah Bangkalan, 2018)
Such a way of thinking was immediately followed by some Muslims especially the ulamas. So that some scholars give special attention by making works that are focused on studying the wisdom, philosophy and wisdom of the Shari'a. like Al Jurjawi with his book Hikmatu Tasyri 'Wafalsafatuhu, Mustafa As Siba'I with his work AhkamuS Shiyam Wa Falsafatuhu, Ad Dahlawy with his work Hujjatullah Al Balighah and other scholars. For this reason, the wisdom and wisdom of Shari'a are very urgent to be revealed in this contemporary era. Through this article the author feels the need to give a little review even though only a small part of the ocean of knowledge and the Shari'a of God which is applied to this people is about the wisdom of the Shari'a and wisdom in the obligation of fasting